Nutritional habits among high-performance endurance athletes - Baranauskas, M.; Stukas, R.; Tubelis, L.; Zagminas, K.; Surkiene, G.; Svedas, E.; Giedraitis, V. R.; Dobrovolskij, V.; Abaravicius, J. A. (Medicina, 2015)
For athletes, the main purpose of nutrition is to ensure the compensation of increased energy consumption and the need for nutrients in the athlete`s body, thereby enabling maximum adaptation to physical loads. The aim of this study was to determine the habits of highly trained endurance athletes depending on sports type, sex and age in order to improve the planning and management of the training of athletes using targeted measures. In 2009-2012, the dietary habits of 146 endurance athletes were analyzed. The actual diet of Lithuania endurance athletes was investigated using a 24-h dietary survey method. Data on the athletes` actual diet were collected for the previous day. It was found that 80.8% of endurance athletes used lower-than-recommended amounts of carbohydrates in their diet, and more than 70% of athletes used higher-than-recommended levels of fat, saturated fatty acids, and cholesterol. The diet of female athletes was low in carbohydrates, dietary fiber, protein, omega-3 fatty acids, B vitamins, potassium, calcium, phosphorus, iron, manganese, and zinc. Athletes aged 14-18 years tended to consume quantities of protein that were either lower than recommended or excessive. The diet of highly trained endurance athletes does not fully meet their requirements and in this situation cannot ensure maximum adaptation to very intense and/or long-duration physical loads. The diet of highly trained endurance athletes must be optimized, adjusted and individualized. Particular attention should be focused on female athletes.